Molecular docking study of ginger (Zingiber officinale) on Immunoglobulin A for smoking cessation - Rika Mayasari Alamsyah; Mieke Hemiawati Satari; Sondang Pintauli; Shelly Iskandar (Pensoft Publishers, 2024)
Smoking is a big problem that can cause death throughout the world. The main ingredient in cigarettes, nicotine, is toxic to humans in several ways. Quitting smoking with the help of medication is associated with adverse side effects such as drowsiness, dry mouth, and nausea. The option of quitting smoking with herbal concoctions such as Zingiber officinale is the recommended choice. The active components of ginger are gingerol and shogaol, which are responsible for their pharmacological effects on immunoglobulin A, which can improve the immune system. The method used is molecular docking, which looks at the stability of human secretory immunoglobulin A when interacting with gingerol and bupropion, which are used as comparison compounds. Molecular docking findings of all herbal material samples revealed that almost all bioactive substances had lower binding energies than immunoglobulin A, especially proteins with PDB IDs 6UE7 and 6UEA. However, only a few ginger-derived bioactive compounds interacting with the 6UEA protein show binding energy values smaller than -7 ± 0.5 kcal/mol. The compounds 8-Gingerol, 8-Shogaol, 6-Shogaol, 6-Gingerol, 5-Shogaol, and 4-Shogaol were able to target the immunoglobulin A receptor protein better than the control, although not as good as the native ligand. Gingerol and Bupropion compounds have stable RMSD and RMSF values compared to human secretory immunoglobulin A without the ligand.